Psychological Empowerment and Change Self-Efficacy As Mediators Between Change Leadership and Affective Commitment to Change - Mangundjaya, Wustari L.; Putri, Elisyah Muliani; Shafira, Aisha (Jurnal Sains Psikologi, 2023)
The world is changing, and the changes are affecting organizations to adapt to the changing as well. However, not all the change initiative programs will succeed due to employees’ lack of commitment to change. The study aims to identify the role of psychological empowerment and change self-efficacy as mediators between change leadership and affective commitment to change. This study surveyed four NGOs with 113 respondents. Data was collected using four types of questionnaires: affective commitment to change, change leadership, change self-efficacy, organizational change, and psychological empowerment. Results showed that change leadership had affected affective commitment to change directly through self-efficacy as a mediator. In the meantime, psychological empowerment could not mediate change leadership and affective commitment to change, as psychological empowerment did not significantly influence affective commitment to change, which can be said that change self-efficacy is more significant than psychological empowerment in terms of affective commitment to change. Results were beneficial for organizations and management to prepare the change initiative effectively in times of organizational change. In this regard, preparing a leader to become an effective change leader is needed to develop an affective commitment to the change of the employees.